Functional genes as markers for sulfur cycling and CO2 fixation in microbial communities of hydrothermal vents of the Logatchev field - Huegler, Michael; Gaertner, Andrea; Imhoff, Johannes F (FEMS MICROBIOLOGY ECOLOGY, 2010)
Life at deep-sea hydrothermal vents depends on chemolithoautotrophic microorganisms as primary producers mediating the transfer of energy from hydrothermal fluids to higher trophic levels. A comprehensive molecular survey was performed with microbial communities in a mussel patch at the Irina II site of the Logatchev hydrothermal field by combining the analysis of 16S rRNA gene sequences with studies of functional key genes involved in biochemical pathways of sulfur oxidation-reduction (soxB, aprA) and autotrophic carbon fixation (aclB, cbbM, cbbL). Most significantly, major groups of chemoautotrophic sulfur oxidizers in the diffuse fluids differed in their biosynthetic pathways of both carbon fixation and sulfur oxidation. One important component of the community, the Epsilonproteobacteria, has the potential to grow chemoautotrophically by means of the reductive tricarboxylic acid cycle and to gain energy through the oxidation of reduced sulfur compounds using the Sox pathway. The majority of soxB and all retrieved aclB gene sequences were assigned to this group. Another important group in this habitat, the Gammaproteobacteria, may use the adenosine 5'-phosphosulfate pathway and the Calvin-Benson-Bassham cycle, deduced from the presence of aprA and cbbM genes. Hence, two important groups of primary producers at the investigated site might use different pathways for sulfur oxidation and carbon fixation.
Keywords: ROV Jason (Remotely Operated Vehicle)